LAND BANK 2.0: AN EMPIRICAL EVALUATION1. (25th August 2015) - Whitaker, Stephan; Fitzpatrick, Thomas J.
ABSTRACT: In 2009, Cuyahoga County, Ohio (Cleveland and 58 suburbs), established a land bank to acquire low‐value properties, mitigate blighted housing, and slow the decline of property values. This empirical study evaluates the effectiveness of the land bank by estimating spatially corrected hedonic price models using sales near the land‐bank homes. The land bank reduces the negative externalities of the properties it acquires. Its largest impact is the preservation of equity in unsold homes. We also estimate the recovered value for homes sold during the study period and the property tax revenue that may have been forgone, absent the land bank.